Native angiosperms documented in the literature for the State of Mexico, Mexico - Martínez-De La Cruz, Isabel; Villaseñor, José Luis; Aguilera Gómez, Luis Isaac; Rubí Arriaga, Martín (Instituto de Ecología, A.C., 2018)
Background and Aims: The richness of vascular plants in the State of Mexico was published for the first time in 1979. Since then, these data have become outdated due to the increasing number of floristic contributions. The objective of this work is contributing to the knowledge of the flora of the State of Mexico, from the available floristic-taxonomic literature.Methods: A database was integrated with information from 351 publications. A map was drawn illustrating the geographical location of floristic inventories and the floristic similarities between these inventories was determined using the Sørensen index.Key results: A list of 169 families, 1103 genera and 3924 species of angiosperms was compiled, where Asteraceae (153 genera and 588 species), Fabaceae (82 and 372), Poaceae (85 and 340) and Orchidaceae (70 and 231) are the best represented families. Muhlenbergia (54 species), Salvia (53) and Ipomoea (51) had the highest number of species. Unpublished theses account for 80% of the taxa. The similarity index revealed that most species are restricted to one or two compilations. The distribution of botanical exploration sites is not uniform, more floristic work has been realized in the southern and southwestern areas. Research has been carried out mainly on sites close to roads and educational institutions of importance. The mountainous regions are poorly explored.Conclusions: The information on angiosperm richness accumulated in the literature is fundamental to determine the geographical distribution of species in the municipalities of the state, to add information on endemism, current and potential uses, as well as to establish conservation programs of its natural resources.